Adoption of Mobile Banking Services: Digital Natives and Digital Immigrants - Çakıroğlu, Arzu Deniz (Fırat University, 2023)
The technological and digital transformation in the world has brought Innovations such as online shopping, e-books, smart watches and mobile services. In the way of consumers the adoption of these digital Innovations, including mobile banking services, does not occur at the same pace for everyone. Individuals born into technology (digital natives) and individuals trying to keep up with digital change (digital immigrants) have different attitudes towards adopting these Innovations. Immigrants may be more distant, while digital natives are closer to adopting Innovations. In this research, it is aimed to determine the differences in terms of adopting mobile banking services between digital natives and digital immigrants based on the dimensions in the Technology Acceptance Model. In addition, the relationships between the demographic characteristics of consumers in both groups and their attitudes towards adopting mobile banking services were also examined. For this purpose, a survey study was conducted in the province of Istanbul. A total of 404 questionnaires were applied. The data obtained from the questionnaires were analyzed using the SPSS 23.0 statistical program. Descriptive statistics, t-test, factor analysis and correlation analysis were used in the analysis of the data. According to the results, digital natives think that using mobile banking services is more advantageous, practical, fast and compatible with their lifestyles than digital immigrants. Digital immigrants, on the other hand, think that using such services is risky compared to digital natives and they are worried.

Dünyada yaşanan teknolojik ve dijital dönüşüm, çevrimiçi alışveriş, e-kitap, akıllı saat, mobil hizmetler gibi yenilikleri de beraberinde getirmiştir. Tüketici açısından değerlendirildiğinde, mobil bankacılık hizmetlerinin de içinde yer aldığı bu dijital yeniliklerin benimsenmesi herkes için aynı hızda gerçekleşmemektedir. Teknolojinin içine doğan bireyler (dijital yerliler) ile dijital değişime ayak uydurmaya çalışan bireylerin (dijital göçmenler) bu yenilikleri benimsemeye yönelik tutumları farklıdır. Dijital yerliler yenilikleri benimsemeye daha yakınken göçmenler daha uzak olabilmektedirler. Bu araştırmada Teknoloji Kabul Modelindeki boyutlar esas alınarak dijital yerliler ve dijital göçmenler arasında mobil bankacılık hizmetlerini benimseme faktörleri açısından farklılıkların belirlenmesi amaçlanmıştır. Ayrıca her iki gruptaki tüketicilerin demografik özellikleriyle mobil bankacılık hizmetlerini benimsemeye yönelik tutumları arasındaki ilişkiler de incelenmiştir. Bu amaçla İstanbul ilinde bir anket çalışması yürütülmüştür. Toplam 404 anket uygulanmıştır. Anketlerden elde edilen veriler SPSS 23.0 istatistik programı kullanılarak analiz edilmiştir. Verilerin analizinde tanımlayıcı istatistikler, t-testi, faktör analizi ve korelasyon analizi kullanılmıştır. Elde edilen sonuçlara göre dijital yerliler dijital göçmenlere göre mobil bankacılık hizmetlerini kullanmanın daha avantajlı, pratik, hızlı ve yaşam tarzlarıyla uyumlu olduğunu düşünmektedirler. Dijital göçmenler ise dijital yerlilere göre bu tür hizmetleri kullanmanın riskli olduğunu düşünmekte ve endişe duymaktadırlar.
MOBİL BANKACILIK HİZMETLERİNİN BENİMSENMESİ: DİJİTAL YERLİLER VE DİJİTAL GÖÇMENLER